2011
DOI: 10.4193/rhino10.136
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory bulb volume and olfactory function in patients with multiple sclerosis

Abstract: BACKGROUND: Some studies reported olfactory dysfunction in patients with multiple sclerosis (MS). There is no agreement about the most suitable testing method for measuring olfactory function (OF) in MS patients. Recent studies showed that olfactory bulb volume changes with the degree of olfactory dysfunction. We assessed olfactory bulb volume of MS patients with magnetic resonance imaging (MRI) and related it to the OF. MATERIAL AND METHODS: Volumetric measurements of the right and left olfactory bulb (OB) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 22 publications
(30 reference statements)
0
24
0
Order By: Relevance
“…Olfactory dysfunctions are reported to have strong correlations with MS. Not only do MS patients show higher levels of olfactory impairment but they also forfeit this ability as their disease progress, which might be due to a lot of underlying factors such as extensive demyelination, accumulating plaque burden, and increasing cognitive impairments [ 1 , 36 , 41 ]. That is why the idea of using olfactory screening tests as a diagnostic and prognostic marker is capturing more and more interest every day [ 32 , 33 , 35 ]. To our knowledge, this is the first systematic review and meta-analysis on the prevalence of olfactory dysfunction in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory dysfunctions are reported to have strong correlations with MS. Not only do MS patients show higher levels of olfactory impairment but they also forfeit this ability as their disease progress, which might be due to a lot of underlying factors such as extensive demyelination, accumulating plaque burden, and increasing cognitive impairments [ 1 , 36 , 41 ]. That is why the idea of using olfactory screening tests as a diagnostic and prognostic marker is capturing more and more interest every day [ 32 , 33 , 35 ]. To our knowledge, this is the first systematic review and meta-analysis on the prevalence of olfactory dysfunction in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…55 Studies have used different methodologies but associations with age, sex, 430,441,447,453 and mood disorders 429,434,435,440,441 have been observed. Association with disease activity, 427,435,437,441,442,444,445,[447][448][449][450]452,453,[457][458][459][460]462,467,468,470,471,473,474 neurological manifestations, 435,[437][438][439][440][441][442][443]445,447,450,452,453,[457][458]…”
Section: G Related To Underlying Systemic Disease 1 Autoimmunementioning
confidence: 99%
“…Another MRI-based study demonstrated that patients with MS with decreased olfactory bulb volumes demonstrated greater olfactory impairment, with a clear correlation between volume and olfactory function. 40…”
Section: Discussionmentioning
confidence: 99%